How Digital Are Albanian Enterprises: A Microeconomic Analyses - Ermira Kalaj; Flora Merko (RTU 62nd International Scientific Conference on Economics and Entrepreneurship, SCEE'2021 Proceedings, 2021)
This paper focuses on the analyses of the digitalization of enterprises and its performance impact in Albania. Using data from 2019 Enterprise Surveys (ES) we try to give answer questions related to digitalization that characterize Albanian enterprises. The survey was a shared project of the European Bank for Reconstruction and Development (EBRD), the European Investment Bank (EIB), and the World Bank Group (WBG). The data are collected in Albania between January and May 2019. The objective of the survey is to better understand firms` experience in the private sector. Collected data are based on firms' experiences and perceptions of the environment in which they operate. The paper uses these specific questions to study Internet adoption. ES questionnaires focus on the following questions: (1) Does the firm have a high-speed Internet connection on its premises? (2) Does the establishment have its website? The dependent variable is the performance of the firms measured in terms of sales growth and labor productivity, while the vector of independent variables is composed of enterprise characteristics such as firm size, ownership structure, legal status, region, etc. Moreover, dummy variables are used to capture access to formal banking services and gender ownership.
Keywords: L15; L25; L26; L86; 330; Information; Firm Performance; Entrepreneurship; Digitalization